If it's not what You are looking for type in the equation solver your own equation and let us solve it.
65-98+(85-6x)=9
We simplify the equation to the form, which is simple to understand
65-98+(85-6x)=9
Remove unnecessary parentheses
+65-98+85-6x=+9
We move all terms containing x to the left and all other terms to the right.
-6x=+9-65+98-85
We simplify left and right side of the equation.
-6x=-43
We divide both sides of the equation by -6 to get x.
x=7.16666666667
| (9x^3-4x^2+3x)-(7x^2+2x+4)= | | 3x/4-21x/32=9/8 | | 12.4=9+t | | -2(2)+9=-(-4)-3 | | 4(y-1/2)=y-6(5-Y) | | 3x/4-21x/32=-11/8 | | 4=-5/x-6 | | 10x+28=4x+178 | | (9b-5)-4(2b+2)=-3 | | 4x-8=-11 | | -5(3)+15=-10(3) | | 5z+5=5z+5 | | 185-6x=30x+17 | | -5(-1)+15=-10(1) | | 9+2z-8=9z+3-5z | | 2x-1=9x+78 | | 3(x+9)=7(x-23) | | 18a+31b+14a-2b= | | -5(2)+15=-10(7) | | x+2+x=-2 | | 6x-1(5x+5)=-8-2(x+12) | | 7-1/3 | | 6*9=n | | 6*8=n | | 5/4x-5/6x | | 3x+3=23-7x | | 3x+1/2(4x+8) | | 16x-6x-2x=0 | | 12(0)-6(3)=-18 | | 2x+(-2)*y=12 | | A*a=B*b | | 12(1)-6(5)=-18 |